2017
DOI: 10.1038/s41598-017-04500-3
|View full text |Cite
|
Sign up to set email alerts
|

Explicit instructions and consolidation promote rewiring of automatic behaviors in the human mind

Abstract: One major challenge in human behavior and brain sciences is to understand how we can rewire already existing perceptual, motor, cognitive, and social skills or habits. Here we aimed to characterize one aspect of rewiring, namely, how we can update our knowledge of sequential/statistical regularities when they change. The dynamics of rewiring was explored from learning to consolidation using a unique experimental design which is suitable to capture the effect of implicit and explicit processing and the proactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 22 publications
3
41
0
Order By: Relevance
“…Rapid statistical learning has also been reported before: for instance, in the ASRT study of Szegedi-Hallgató et al (2017), statistical learning was apparent already in the first epoch in the Explicit group but seemed to have larger individual differences in the Implicit groups as only one of the two Implicit groups exhibited significant statistical learning in the first epoch (see Supplementary results and figures in Szegedi-Hallgató et al, 2017). Similarly, in Kóbor et al (2018) study, statistical learning was observed in the first epoch of the explicit version of the ASRT task, along with a significant sequence learning as well.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Rapid statistical learning has also been reported before: for instance, in the ASRT study of Szegedi-Hallgató et al (2017), statistical learning was apparent already in the first epoch in the Explicit group but seemed to have larger individual differences in the Implicit groups as only one of the two Implicit groups exhibited significant statistical learning in the first epoch (see Supplementary results and figures in Szegedi-Hallgató et al, 2017). Similarly, in Kóbor et al (2018) study, statistical learning was observed in the first epoch of the explicit version of the ASRT task, along with a significant sequence learning as well.…”
Section: Discussionsupporting
confidence: 68%
“…Consequently, a possible explanation for the very rapid statistical learning is that, in an explicit condition, the instructions and motivation to learn can have an overarching effect, providing a cognitive state, in which not only the instructed sequential but also the uninstructed statistical regularities can be learned quickly. Although this was not in the primary focus of these previous studies, if we take a closer look at the learning trajectories, it appears that statistical regularities are extracted very early and no (or very little) further gains may be observed during training if explicit instructions are given for the sequential information (Szegedi-Hallgató et al, 2017; Kóbor et al, 2018). In contrast, in the implicit conditions, statistical learning may undergo further improvements during training (Szegedi-Hallgató et al, 2017), above and beyond the strengthening of the acquired knowledge as suggested in the previous paragraph.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, a possible explanation for the very rapid statistical learning is that, in an explicit condition, the instructions and motivation to learn can have an overarching effect, providing a cognitive state, in which not only the instructed sequential but also the uninstructed statistical regularities can be learned quickly. Although this was not in the primary focus of these previous studies, if we take a closer look at the learning trajectories, it appears that statistical regularities are extracted very early and no (or very little) further gains may be observed during training if explicit instructions are given for the sequential information (Szegedi- Hallgató et al, 2017;Kóbor et al, 2018). In contrast, in the implicit conditions, statistical learning may undergo further improvements during training (Szegedi- Hallgató et al, 2017), above and beyond the strengthening of the acquired knowledge as suggested in the previous paragraph.…”
Section: Discussionmentioning
confidence: 98%
“…Although this was not in the primary focus of these previous studies, if we take a closer look at the learning trajectories, it appears that statistical regularities are extracted very early and no (or very little) further gains may be observed during training if explicit instructions are given for the sequential information (Szegedi- Hallgató et al, 2017;Kóbor et al, 2018). In contrast, in the implicit conditions, statistical learning may undergo further improvements during training (Szegedi- Hallgató et al, 2017), above and beyond the strengthening of the acquired knowledge as suggested in the previous paragraph. These observations support the interpretation that explicit instructions and the motivation to learn can have an overarching effect in that not only the instructed sequential but also the uninstructed statistical regularities can be learned more quickly.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation